Sol-gel combustion synthesis and characterization studies of manganese (International Journal of Food and Nutritional Sciences, 2022)
Spinel ferrite nanoparticles presents fascinating application on biomedical, which aimed us to focus the recent investigations on synthesis of pure and manganese substituted nickel ferrite(Ni1-xMnxFe2O4; x = 0.0, 0.5) nanoparticles using sol-gel combustion technique. The structure and the average crystallite size of the synthesized nanoparticles were analyzed from Powder X-Ray Diffraction studies. The vibrational bands corresponding to metal-oxygen linkage detected between 300-700 cm-1 were noticed from FT-IR spectral analysis. TEM analysis was used to study the morphology of the synthesized nanoparticles.